Islamic Religious Education Curriculum with a Multicultural Insight in Elementary Schools - Rahmat, Rahmat (Anjasmoro: Islamic Interdisciplinary Journal, 2023)
The Islamic Religious Education (PAI) Curriculum with a Multicultural Insight is a brilliant idea to be realized in determining the direction of the Islamic Religious learning process at both the Elementary School (SD) and/or Madrasah Ibtidaiyah (MI) levels considering that Indonesia has a rich culture, ethnicity, language and so on, especially the participants Elementary school and Madrasah Ibtidaiyah students are the ideal first generation to start implementing the internalization of multicultural values. PAI learning with a multicultural perspective itself prioritizes the internalization and implementation of multicultural values ​​into Islamic Religious Education learning in schools and Islamic Religious learning in madrasas. This research utilized qualitative research library research, and the results of this research were obtained, 1) Learning Islamic Religious Education at the elementary school level is very important to be implemented with the process of internalizing multicultural values, and 2) Furthermore, for this multicultural insight a curriculum is needed The appropriate one is the Islamic Religious Curriculum (PAI) with a multicultural perspective, where in practice the preparation and adjustment of the curriculum is then implemented in learning which can measurably have implications for students who at least have a multicultural attitude, namely an attitude of respecting and appreciating differences.